Perceptions of Millennials on Filipino Superstitious Belief - Adonis S. Besa; Hassanal P. Abusama; Genebelle M. Lao; Elyza G. Abraham; Fareeda de la Cruz; Sheena L. Duldulao; Seth Nahzier S. Perocho (Universitas Pendidikan Indonesia (UPI), 2021)
This study aims to cater to the millennials' perceptions of Filipino Superstitious Beliefs and how they can affect one person's behavior and performance. The study investigated the following questions: (1) What are the reasons why the chosen respondents believe in superstitions? (2) What are the effects of superstitions on the lives of millennials? (3) What are the perspectives of millennials nowadays on some Filipino superstitious beliefs? (4) How can superstitious beliefs affect one person’s performance and behavior? We used the qualitative method, specifically phenomenological in the research design. We conducted interviews and questionnaires. Data was recorded, analyzed, classified, and organized using necessary measurements and analyses. Believing in superstitions can be one of the basic traditions that are taught to Filipinos while they growing up. It is proven that not all millennials have forgotten the sense of believing in some Filipino superstitious beliefs. All responses from the participants had different senses of values. They also do have the same idea on how they can give back respect to our ancestors. Being superstitious can influence perspectives, giving impact to everything for making execution and decision. Indeed, it is on a specific test to the response to fake treatments. The study found out that millennials still believe in the power of superstitions based on their experiences, the traditions of their old ones, or even the ancestors. This study is an approach to clarify the understanding of superstitions in the current time.